Drosophila jun relays the jun amino-terminal kinase signal transduction pathway to the decapentaplegic signal transduction pathway in regulating epithelial cell sheet movement. - Hou, X.S.; Goldstein, E.S.; Perrimon, N. (Genes & Development, 1997)
We have characterized mutations in the Drosophila homolog of the mammalian proto-oncogene c-Jun gene (Djun). We demonstrate that DJUN in the embryo is a downstream target of the JNK signal transduction pathway during dorsal closure formation, and that the function of the JNK/DJUN pathway is to control the localized expression of decapentalegic (dpp), a member of the TGF-beta growth factor family. In contrast to previous observations, we find that both in the embryo and during photoreceptor cell determination, DJUN is not regulated by a pathway that involves MAPK.